2012
DOI: 10.1080/10550887.2012.735563
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Drug Abuse Patterns of Treatment-Seeking Illicit Drug Abusers in Finland, 1997–2008: The Huuti Study

Abstract: The epidemiological part of the Huume tietokanta (HUUTI) consortium research project is the first large-scale longitudinal study of treatment-seeking illicit drug abusers in Finland. The objective of this report was to describe the sociodemographic characteristics and drug abuse patterns of treatment-seeking clients at their first visit. This study analysed baseline data of 4817 clients (3365 men and 1452 women) aged 11-65 years who sought treatment for drug abuse between 1997 and 2008 at Helsinki Deaconess In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
5
30
1
Order By: Relevance
“…Among the samples from Centres A and B the mean numbers of concurrently abused drugs per sample were 2.1 and 3.9, respectively. In the survey by Onyeka et al ., the mean number of concurrent drugs for Finnish treatment‐seeking drug abusers was 3.5. Polydrug abuse has been shown to increase the risk of premature termination of OMT .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the samples from Centres A and B the mean numbers of concurrently abused drugs per sample were 2.1 and 3.9, respectively. In the survey by Onyeka et al ., the mean number of concurrent drugs for Finnish treatment‐seeking drug abusers was 3.5. Polydrug abuse has been shown to increase the risk of premature termination of OMT .…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, 101 NPS were reported to the European Union Early Warning System . A large‐scale Finnish survey on treatment‐seeking drug abusers showed that stimulants previously used to be the most frequently abused drugs, but nowadays the primary drugs of abuse are injected opioids . In addition, polydrug abuse was common, the mean number of substances abused being 3.5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of drug use patterns among all the clients have been described elsewhere [27] but a brief description is provided here. Lifetime prevalence was highest for cannabis (78%).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals abuse prescription medicines for various reasons that may include: in order to get high; as selfmedication for anxiety, pain, or sleep problems; or to enhance cognition [7]. It could also be used as secondary drug among those who abuse alcohol and illicit drugs [8]. However, these reasons/purposes may vary by gender, age and other factors.…”
Section: Introductionmentioning
confidence: 99%